2012
DOI: 10.1016/j.arr.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin: Roles in cancer and senescence

Abstract: Cancer and senescence are both complex transformative processes that dramatically alter many features of cell physiology and their interactions with surrounding tissues. Developing the wide range of cellular features characteristic of these conditions requires profound alterations in global gene expression patterns, which can be achieved by suppressing, activating, or uncoupling cellular gene regulatory pathways. Many genes associated with the initiation and development of tumors are regulated at the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 153 publications
(194 reference statements)
0
57
0
Order By: Relevance
“…TTP is also induced by mitogens and functions to attenuate the expression of a subset of mitogeninduced ARE-containing transcripts (64,65). Our data suggest that RNase L functions in association with TTP to degrade SRF mRNA providing a mechanism to limit SRF-induced transcription.…”
Section: Rnase L and Ttp Function To Down-regulate The Expression Of mentioning
confidence: 78%
See 2 more Smart Citations
“…TTP is also induced by mitogens and functions to attenuate the expression of a subset of mitogeninduced ARE-containing transcripts (64,65). Our data suggest that RNase L functions in association with TTP to degrade SRF mRNA providing a mechanism to limit SRF-induced transcription.…”
Section: Rnase L and Ttp Function To Down-regulate The Expression Of mentioning
confidence: 78%
“…However, the functional significance of this regulation and the biologic contexts in which it occurs are not known. The major biologic functions attributed to TTP occur following the induction of its expression or activity by diverse stimuli, including mitogens (7,64,65). In light of the overlapping roles for RNase L and TTP in antiproliferative and tumor suppressor activities, we examined the regulation of TTP by RNase L in the context of mitogen stimulation as a potential mechanism by which the proliferative response is attenuated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tristetraprolin can destabilize TNFα and vascular endothelial growth factor mRNAs. 131 Tristetraprolin induces senescence in human papillomavirus-transformed cervical cancer cells by targeting E6-AP ubiquitin ligase. 132 However, it remains unknown whether tristetraprolin is involved in vascular aging.…”
Section: Degradation Of Nucleic Acids and Agingmentioning
confidence: 99%
“…This was confirmed by the observations that treatment with anti-TNF antibodies or interbreeding the TTP KO mice with mice lacking both TNF receptors prevented the development of the inflammatory phenotype (7,8). Subsequent studies on bone marrow-derived macrophages from these animals demonstrated that the TNF mRNA is a direct target of TTP and that the binding of TTP to binding sites in the 3=UTR of TNF mRNA could promote its decay (9, 10).Since the early demonstration of TNF mRNA as an important physiological target of TTP, many other mRNAs have been identified as real or potential TTP targets (11)(12)(13)(14). Many of these putative target transcripts have been identified and studied in primary cells derived from the TTP KO mice or in cultured cells in which TTP was knocked down by other techniques.…”
mentioning
confidence: 99%